Click Silicones - Yu, Gilbert (My University, 2008)
Both the thermal and copper(I) catalyzed azide-alkyne Huisgen cycloadditions were explored as strategies to be used for silicone functionalization and crosslinking. The generality of these reactions was demonstrated (Chapter 2) using 1,3-bis(azidopropyl)tetramethyldisiloxane (BAPTMDS) as a model compound. The ligation of this compound with several alkyne-containing molecules, especially the copper(I) catalyzed process or “click” proved to be easy to perform, high yielding, and gave the 1,4-triazole regioisomer as the sole product. Thermal, metal catalyst-free, azide-alkyne cross-linking (Chapter 3) using a poly(azidopropylmethylsiloxane)-co-dimethylsiloxane as the base polymer and several polysubstituted alkyne molecules as crosslinkers was efficient. The reaction of the base polymer with an ethynyl-terminated disiloxane demonstrates that a silicone elastomer can be synthesized by simple heating and that the resulting material is stable, decomposing only at temperatures higher than 230 °C. Finally, direct bioconjugation of silicones to biotin using propargylamide and BAPTMDS was examined (Chapter 4). The result of the copper(I) catalyzed Huisgen ligation of biotin onto silicones was as efficient as the reactions in the previous chapters, revealing that the “click” process can successfully be applied to a broad range of silicones.
Keywords: silicones; click process; silicione functionalization; silicone crosslinking